2018
DOI: 10.1103/physrevlett.121.088101
|View full text |Cite
|
Sign up to set email alerts
|

Bend-Induced Twist Waves and the Structure of Nucleosomal DNA

Abstract: Recent work indicates that twist-bend coupling plays an important role in DNA micromechanics. Here we investigate its effect on bent DNA. We provide an analytical solution of the minimum-energy shape of circular DNA, showing that twist-bend coupling induces sinusoidal twist waves. This solution is in excellent agreement with both coarse-grained simulations of minicircles and nucleosomal DNA data, which is bent and wrapped around histone proteins in a superhelical conformation. Our analysis shows that the obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 36 publications
(41 reference statements)
1
74
0
Order By: Relevance
“…The oscillations in the bending densities Ω 1 and Ω 2 arise from the geometrical constraints of the system, which in turn induce oscillations in the twist density Ω 3 from the presence of twist-bend coupling (G = 0). These twist waves have been indeed observed in X-ray crystallographic structures of DNA bound to histone proteins [18]. While Eq.…”
Section: Dna Elasticity and Twist-bend Couplingmentioning
confidence: 59%
See 3 more Smart Citations
“…The oscillations in the bending densities Ω 1 and Ω 2 arise from the geometrical constraints of the system, which in turn induce oscillations in the twist density Ω 3 from the presence of twist-bend coupling (G = 0). These twist waves have been indeed observed in X-ray crystallographic structures of DNA bound to histone proteins [18]. While Eq.…”
Section: Dna Elasticity and Twist-bend Couplingmentioning
confidence: 59%
“…We focused particularly on the effect of twist-bend coupling, which is an interaction arising from the DNA grooves asymmetry [15]. As recently discussed in the case of DNA minicircles and nucleosomal DNA [18], we found that also in DNA loops the bending deformation induces twist waves, i.e., twist oscillations following the periodicity of the helical pitch. Differently from the minicircle case, in the loops discussed here twist waves have a modulated amplitude, which is maximal at the loop apex and vanishes at the two ends.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The physical implications of this coupling are profound and mechanically akin to those described in §3. For instance, if a protein such as RNAP ( figure 5 ) bends the DNA locally, this mechanical deformation propagates in the form of mechanical twist waves down the chain [ 138 ]. These waves are reminiscent of soliton solutions in the PB-like models described above and have important implications for the stability of nucleosomes, the complex of DNA and histone proteins, which makes the chromatin in eukaryotic cells [ 138 ].…”
Section: Computational Challenges and Models For Dna Dynamicsmentioning
confidence: 99%